Adsorption analysis : equilibria and kinetics - Duong, D. Do. (London : Imperial College Press, 1998)
This book covers topics of equilibria and kinetics of adsorption in porous media. Fundamental equilibria and kinetics are dealt with for homogeneous as well as heterogeneous particles. Five chapters of the book deal with equilibria and eight chapters deal with kinetics. Single component as well as multicomponent systems are discussed. In kinetics analysis, we deal with the various mass transport processes and their interactions inside a porous particle. Conventional approaches as well as the new approach using Maxwell-Stefan equations are presented. Various methods to measure diffusivity, such.
3.10.3 De Boer Method3.11 Assessment of Pore Shape; 3.11.1 Hysteresis Loop; 3. 11.2 t-Method; 3.11.3 The s Method; 3.12 Conclusion; 4 Pure Component Adsorption in Microporous Solids; 4.1 Introduction; 4.1.1 Experimental Evidence of Volume Filling; 4.1.2 Dispersive Forces; 4.1.3 Micropore Filling Theory; 4.2 Dubinin Equations; 4.2.1 Dubinin-Radushkevich (DR) Equation; 4.2.2 Dubinin-Astakhov Equation; 4.2.3 Isosteric Heat of Adsorption and Heat of Immersion; 4.3 Theoretical Basis of the Potential Adsorption Isotherms; 4.4 Modified Dubinin Equations for Inhomogeneous Microporous Solids.
Includes bibliographical references (pages 879-888) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Adsorption; Porous materials; Gases -- Absorption and adsorption; Solids -- Surfaces; Chemical engineering -- Data processing; Adsorption; Adsorption; Gaz -- Absorption et adsorption; Génie chimique -- Informatique; adsorption; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; SCIENCE -- Chemistry -- Industrial & Technical; Adsorption; Chemical engineering -- Data processing; Gases -- Absorption and adsorption; Porous materials; Solids -- Surfaces